Rancang bangun Sistem Pendeteksi Banjir pada Sungai Lamandau di Nanga Bulik Berbasis Website dan IOT (Internet Of Things) - Harnanda, Brian Pratama (JATISI, 2024)
The occurrence of overflow of water to land in large quantities caused by excessive rainfall in areas along the river flow resulting in flooding in low areas resulting in losses for affected communities in Nanga Bulik city, Bulik District, Lamandau Regency.Because the area is directly adjacent to the flow of the Lamandau River, Batu Pier can be determined as an observation point for the water level of the Lamandau River and also as a monitoring point for research on website-based flood detection systems and IoT (Internet Of Things).The research method used is R&D (Research and Development). This research method was created to detect the tendency of high water overflow by connecting a website-based detection system and the Internet of Things (IoT) consisting of a setting menu, graph menu, history menu, and sensor monitoring results.With this system, it helps agencies, institutions, communities in observing and monitoring the water level of the Lamandau River remotely so that there is no need to go to the location of the monitoring point created.